A quick peek at solar cells and a closer insight at perovskite solar cells - Hadeer M. Ali; S.M. Reda; A.I. Ali; M.A. Mousa (Egyptian Journal of Petroleum)
The use of renewable resources including solar energy has become a mandatory approach to reduce the repercussions of the excessive use of fossil fuels. Recently, there has been an exponential increase in the research of solar cells of various types, which led to their storming the international economic market as a safe source of energy. Silicon-based solar cells (Si-based SCs) occupied the throne of solar cells until the advent of perovskite solar cells (PSCs), which captured the attention of scientists around the world with its high and rapid tide in the values of their efficiencies, which exceeds 25% and predicted to reach the Shockley–Queisser limit. This review takes, in summary, a general tour in the world of PSCs to discuss the perovskite emergence and its composition materials, the components of PSCs, the unique properties of hybrid organic–inorganic perovskites (HOIPs) that stand behind the high-performance devices, the PSC architectures and their fabrication processes, the industrial challenges and finally a future view on PSC fate.